Advances in steel-based catalysts for water electrolysis: Mechanisms, modifications, and industrial prospects - Xiaochun WANG; Chao CHEN; Jinping FAN; Enhao LIU; Jinzhou LI; Jie DANG (工程科学学报)
In pursuing carbon peaking, carbon neutrality, and energy transformation, hydrogen energy is increasingly recognized as a renewable and clean source with a high energy density. Currently, hydrogen is primarily produced through the combustion of fossil fuels and as an industrial by-product. This method generates significant amounts of carbon dioxide, earning the label “gray hydrogen.” Conversely, hydrogen derived from water electrolysis using renewable energy sources, such as electricity and solar power, is termed “green hydrogen.” Among various hydrogen production techniques, electrolytic hydrogen production powered by renewable energy is particularly advantageous due to its zero carbon emissions and ability to store surplus electrical energy. This method is a focal point in the ongoing research into hydrogen energy advancements. The water electrolysis process comprises two half-reactions: the oxygen evolution reaction (OER) at the anode and the hydrogen evolution reaction (HER) at the cathode. Typically, a voltage exceeding the theoretical value of 1.23 V (relative to the reversible hydrogen electrode) is required to facilitate the reactions during electrolysis. Therefore, the choice of electrolysis water catalyst is directly related to electrolysis efficiency and hydrogen production cost. Compared with noble metal catalysts, steel-based catalysts offer significant advantages, including lower raw material costs, abundant availability, and enhanced stability, primarily due to their composition of transition metal elements such as Fe, Ni, Co, and Mo. These elements exhibit catalytic activity for both the OER and the HER. Surface modifications significantly enhance their catalytic performance and compatibility with electrolysis devices. Therefore, developing low-cost, high-performance steel-based catalysts is crucial for the widespread industrial application of water electrolysis. This paper first discusses the catalytic mechanism analysis and surface modification techniques of steel-based materials as OER and HER catalysts. The OER catalytic mechanism includes the adsorbate evolution mechanism (AEM) and the lattice oxygen evolution mechanism (LOM). Surface modification methods encompass increasing the reaction area, enriching active materials, and introducing external elements to improve catalytic performance. Enhancing the reaction area provides more active sites on steel-based catalysts, whereas enriching active materials leverages the diverse catalytically active elements inherent in steel. Additionally, transition metal elements are transformed into hydroxides and oxyhydroxides with superior catalytic activity in modification treatments. Introducing heteroatoms not only forms heterojunctions or heterointerfaces on the catalyst surface but also alters the composition and morphology of the catalytic layer, facilitating the loading of various elements. Furthermore, atomic doping can modify the electronic structure of active sites such as Ni and Fe within the steel matrix, thereby enhancing the electrolysis efficiency. Advances in characterization equipment and the application of first-principles calculations in catalytic reactions have led to a deeper understanding of specific active sites and new OER reaction mechanisms, elucidating the reasons behind the impressive catalytic performance of steel-based catalysts. Active investigation into the catalytic mechanisms of steel-based catalysts can guide the development of high-performance catalysts. Subsequently, the paper describes the catalytic mechanisms and primary modification methods for steel-based HER catalysts and summarizes the progress of research on steel-based materials as monofunctional and bifunctional catalysts in total hydrolysis units. The conclusion proposes enhancing the performance and industrial application of steel-based catalysts through theoretical calculations, exploration of catalytic mechanisms, and advanced processing technologies.